Successful extracorporeal membrane oxygenation assisted revascularisation in a high-risk elderly patient refused surgical treatment - Samalavičius, Robertas; Puodžiukaitė, Lina; Abraitis, Vytautas; Norkienė, Ieva; Ščupakova, Nadežda; Pekarskienė, Justina; Zorinas, Aleksejus; Ručinskas, Kęstutis; Šerpytis, Pranas (Acta medica Lituanica, 2020)
Management of high-risk elderly patients requiring revascularisation remains a clinical challenge. We report a case of extracorporeal membrane oxygenation (ECMO) assisted complex percutaneous coronary intervention in a high-risk octogenarian. An 83-yearold female with signs of worsening heart failure was admitted to the emergency department of a tertiary care facility. Transthoracic echocardiography revealed a decreased left ventricular ejection fraction of 20% with severe mitral regurgitation and mild aortic and tricuspid valve insufficiency. Three-vessel disease was found during coronary angiography. Due to the patient’s frailty, a high-risk surgery decision to proceed with ECMO assisted percutaneous coronary intervention was made during a heart team meeting. Following initiation of mechanical support, coronary lesions were treated with three drug-eluting stents. After the procedure, the patient was transferred to the ICU on ECMO support, where she was successfully weaned from the device 9 h later. Her ICU stay was four days. She was successfully discharged from the hospital after uneventful recovery. At one-year’s follow-up, the patient was clinically stable in an overall state of general well-being and with complete participation in routine activities; she had good exercise tolerance and no signs of ischemia. This report highlights the possibility of use of ECMO during PCI in high-risk elderly patients.